THE ROLE OF PEDAGOGICAL TECHNOLOGIES IN THE PREPARATION OF EDUCATORS FOR ACTIVITIES - Xalilova Dildora (The Conference Hub, 2025)
The article describes the application of” pedagogical technologies aimed at activating and accelerating the educational process", the transformation of modern society into a direct productive force in the educational system, ensuring the necessary effectiveness of the educational process and guaranteeing the achievement of the intended results of study by students
Keywords: pedagogical technologies, design of the educational process, method, tool, skill, information telecommunication technologies.